2010
DOI: 10.2353/ajpath.2010.091075
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Role of the E3 Ubiquitin Ligase NEDD4-1, a PTEN Negative Regulator, in Non-Small-Cell Lung Carcinomas

Abstract: Loss of the PTEN tumor suppressor gene occurs frequently in non-small-cell lung carcinoma (NSCLC), although neither genetic alterations nor epigenetic silencing are significant predictors of PTEN protein levels. Since recent reports implicated neural precursor cell expressed, developmentally down-regulated 4-1 (NEDD4-1) as the E3 ubiquitin ligase that regulates PTEN stability, we investigated the role of NEDD4-1 in the regulation of PTEN expression in cases of NSCLC. Our findings indicate that NEDD4-1 plays a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
131
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 127 publications
(133 citation statements)
references
References 35 publications
1
131
1
Order By: Relevance
“…The Nedd4-IRS-2 binding may represent a novel drug target at least in prostate cancer. Accumulating evidence suggests that Nedd4 is overexpressed in various cancers and functions as a tumour-promoting factor [17][18][19][20][21] . It is important to investigate the contribution of the Nedd4-IRS-2 complex to the development of various cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Nedd4-IRS-2 binding may represent a novel drug target at least in prostate cancer. Accumulating evidence suggests that Nedd4 is overexpressed in various cancers and functions as a tumour-promoting factor [17][18][19][20][21] . It is important to investigate the contribution of the Nedd4-IRS-2 complex to the development of various cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Nedd4 knockout mice show fetal growth retardation and perinatal lethality 16 , indicating a crucial role for Nedd4 in embryonic growth. Nedd4 is overexpressed in several types of cancers and functions as an oncogenic protein [17][18][19][20][21] . We provide multiple lines of evidence, suggesting that Nedd4 conjugates monoubiquitin to IRS-2 and recruits IRS-2 to the plasma membrane, thereby enhancing IRS-2 tyrosine phosphorylation by IGF-IR and IGF-I mitogenic activity.…”
mentioning
confidence: 99%
“…44 Antibodies specific for total Akt, phospho-Akt (Ser473) and for caspase3/7, ERK1/2, phospho-ERK1/2 (Thr202/Tyr204), LC3BII were obtained from Cell Signaling Technologies.…”
mentioning
confidence: 99%
“…But the dominant views are still that the oncogenic activity of NEDD4 depends on the degradation of PTEN. Amodio et al 18 have demonstrated that NEDD4 is overexpressed in human NSCLC, and the overexpression of NEDD4 leads to an increase of the ubiquitylated form of PTEN, thereby reducing PTEN levels and increasing Akt activation. Ahn et al 35 also confirmed that NEDD4 can inhibit PTENinduced apoptosis in cells; in addition, PTEN can act as a feedback regulator for NEDD4 and transcriptionally regulate the expression of NEDD4.…”
Section: Discussionmentioning
confidence: 99%
“…17 Inverse relationships between the expression of NEDD4 and PTEN have also been observed in human NSCLC. 18 However, recent work failed to find the relationship between NEDD4-mediated PTEN degradation and acquired resistance to EGFR-TKIs in NSCLC.…”
Section: Introductionmentioning
confidence: 99%